2005
DOI: 10.1007/s10534-005-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to high fluoride concentration in drinking water will affect spermatogenesis and steroidogenesis in male albino rats

Abstract: Sodium fluoride (NaF) administered orally to adult male rats at a dose level of 4.5 ppm and 9.0 ppm for 75 days caused significant decrease in the body weight, brain index and testicular index. A significant decrease in sperm count, sperm motility, sperm viability and sperm function (HOS positive) with increased sperm abnormalities was also observed in NaF-exposed male rats. The activity levels of testicular steroidogenic marker enzymes 3beta-hydroxysteroid dehydrogenase (3beta-HSD) and 17beta-hydroxysteroid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 23 publications
5
27
1
2
Order By: Relevance
“…Sodium fluoride (NaF) was shown to elicit physiological effects in numerous clinical and laboratory studies, with the toxicity of NaF decreasing fertility in most animal species tested (Freni, 1994;Ortiz-P erez et al, 2003;Lu et al, 2014). An intensive literature search revealed that fluoride negatively affects sperm function, including morphology, motility, capacitation, and the acrosome reaction (Chinoy et al, 1994;Elbetieha et al, 2000;Pushpalatha et al, 2005; Dvora 0 kova 0 -Hortova 0 et al Izquierdo-Vega et al, 2008;Spittle, 2009;Sun et al, 2010) all of which are the key process in fertilization, both in vitro and in vivo Kwon et al, 2014a). Additionally, according to National Research Council annual report (ShraderFrechette, 2007), fluoride is an endocrine disruptor altering normal endocrine functions thus might affect sperm function by binding to its receptors on spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium fluoride (NaF) was shown to elicit physiological effects in numerous clinical and laboratory studies, with the toxicity of NaF decreasing fertility in most animal species tested (Freni, 1994;Ortiz-P erez et al, 2003;Lu et al, 2014). An intensive literature search revealed that fluoride negatively affects sperm function, including morphology, motility, capacitation, and the acrosome reaction (Chinoy et al, 1994;Elbetieha et al, 2000;Pushpalatha et al, 2005; Dvora 0 kova 0 -Hortova 0 et al Izquierdo-Vega et al, 2008;Spittle, 2009;Sun et al, 2010) all of which are the key process in fertilization, both in vitro and in vivo Kwon et al, 2014a). Additionally, according to National Research Council annual report (ShraderFrechette, 2007), fluoride is an endocrine disruptor altering normal endocrine functions thus might affect sperm function by binding to its receptors on spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Esse defeito espermático pode ter ocorrido como um artefato de coleta, em conseqüência de um possível choque térmico (SILVA et al, 1993). Estudos em animais de laboratório demonstraram que o consumo de NaF na água de beber (5, 10 e 150ppm) diminui a qualidade espermática (CHINOY et al, 1995;CHINOY et al, 1997;PUSHPALATHA et al, 2005;WAN et al, 2006), bem como induz alterações histológicas no epitélio seminífero (WAN et al, 2006). Em um experimento in vitro com sêmen ovino de animais de produção, foi observado decréscimo na motilidade espermática após adição de diferentes concentrações de NaF (20, 100, 200μmol L -1 e 0,1mol L -1 ) (ZAKRZEWSKA et al, 2002).…”
Section: Resultsunclassified
“…The testosterone is an important androgen produced in the testis and is involved in the initiation of spermatogenesis [14]. Many studies have reported the male reproductive defects induced by fluoride, such as the deleterious effects of NaF on testosterone level, spermatogenesis, sperm motility and morphology, and fertilizing ability [1,15,16].…”
Section: Discussionmentioning
confidence: 99%